1997
DOI: 10.1149/1.1837390
|View full text |Cite
|
Sign up to set email alerts
|

Stable High Conductivity Ceria/Bismuth Oxide Bilayered Electrolytes

Abstract: We have developed a high conductivity bilayered ceria/bismuth oxide anolyte/electrolyte that uses the Po gradient to obtain stability at the anolyte-electrolyte interface and reduced electronic conduction due to the electroly3te region. Results in terms of solid oxide fuel cell (SOFC) performance and stability are presented. These results include a 90 to 160 mV increase in open-circuit potential, depending on temperature, with the bilayered structure as compared to SOFCs fabricated from a single ceria layer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 1 publication
(1 reference statement)
3
74
2
Order By: Relevance
“…The density of the film depends on the sintering schedule and the stability of the sol. The cell performance was comparable to those reported in the literature [5,14]. The cathode performance needs improvement and we are developing new cathodes to address this.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The density of the film depends on the sintering schedule and the stability of the sol. The cell performance was comparable to those reported in the literature [5,14]. The cathode performance needs improvement and we are developing new cathodes to address this.…”
Section: Resultssupporting
confidence: 73%
“…operation under both open circuit and maximum power conditions [5]. More recently, we developed an analytical model to determine the defect transport in this bilayer and have found that a bilayer comprised primarily of the more conductive component (bismuth oxide) is stable for 500°C operation [6,7].…”
Section: Esb Decomposesmentioning
confidence: 99%
“…We demonstrated previously that this concept works; that a bismuth oxide/ceria bilayer electrolyte provides near theoretical open circuit potential (OCP) and is stable for 1400 h of fuel cell operation under both open circuit and maximum power conditions [5]. In this project we extended the demonstration of the concept significantly, as described below.…”
Section: Esb Decomposesmentioning
confidence: 88%
“…Table 4. [2][3][4][5][6][7][8] shows that the difference between the jump distances of ordered and disordered structures is highest for Yb and Er doped structures, and lowest for the Dy doped structures. This clearly is consistent with the difference in kinetics of aging for structures with different dopants.…”
Section: Effect Of Structure On Conductivity Pre-exponential Factormentioning
confidence: 99%
See 1 more Smart Citation